A visual analog scale for patient‐reported voice outcomes: The VAS voice. Issue 1 (17th December 2019) - Naunheim, Matthew R.; Dai, Jennifer B.; Rubinstein, Benjamin J.; Goldberg, Leanne; Weinberg, Alan; Courey, Mark S.
Abstract: Objectives: Although patient‐reported outcome measures (PROMs) can be useful for assessing quality of life, they can be complex and cognitively burdensome. In this study, we prospectively evaluated a simple patient‐reported voice assessment measure on a visual analog scale (VAS voice) and compared it with the Voice Handicap Index (VHI‐10). Study design: Prospective survey. Methods: An abbreviated voice measure was designed by a team of otolaryngologists, speech pathologists, and patients that consisted of four VAS questions related to (a) a global question of voice disturbance, (b) physical function of voice, (c) functional issues, and (d) emotional handicap. All English‐speaking patients presenting to an academic laryngology clinic for a voice complaint were included. Internal consistency and validity were assessed with comparison to the VHI‐10. Results: A total of 209 patients were enrolled. Ninety‐two percent of patients reported understanding the survey. The four‐item VAS survey was highly correlated with VHI‐10 score (Pearson correlation .81, P < .0001), and the Cronbach's alpha between all four VAS questions was .94. Age, gender, and diagnosis were not associated with either the global VAS or VHI‐10 tool. Conclusion: Reducing the complexity of instruments assessing voice‐related quality of life is feasible, and the VAS voice correlated with existing measures. Simplified assessments may offer advantages compared to more cumbersome PROMs. Level of Evidence: 2c